Assessment of microplastics contamination in selected coral species from Kuantan coastal waters off the South China Sea - Miskon, Fuad; Sharulnizam, Shamin Amarul; Ghazali, Intan Noor Munira; Mohd Hanapiah, Muhammad Faiz; Rosli, Muhammad Khairulanwar (Universitas Malikussaleh, 2024)
Microplastics, defined as plastic particles less than 5 mm in size, pose a significant environmental threat and have been detected across various terrestrial and marine ecosystems. This study explores the abundance, types, and potential impact of microplastics in corals from the coastal waters of Kuantan, Malaysia. Using Fourier Transform Infrared (FTIR) spectroscopy, three coral species - Acropora, Montipora, and Porites - were collected from two locations, Pulau Ular and Cherok Paloh, to identify and quantify the microplastics contamination. A total of nine samples underwent a digestion process to isolate and analyze microplastics from both external and internal structures. The results revealed that Acropora species exhibited the highest microplastics abundance, while Montipora and Porites showed similar but comparatively lower contamination levels. The identified polymers included polyacrylamide, polyvinyl, polyethylene, polyamide, styrene, polypropylene, methyl vinyl ether, and polystyrene, with polyacrylamide being the most prevalent, constituting 33.33% of the total microplastics detected. These findings align with previous studies and underscore the potential adverse effects on coral feeding mechanisms, energy intake, and overall health. This study highlights the significance of ongoing research to refine microplastic identification methods and to develop targeted strategies to mitigate their impact on marine ecosystems.